Quality attributes of hurdle technology-based shelf-stable chicken pickle fried for different durations - Singh , Shubha; Goswami, Meena; Pathak, Vikas; Verma, Arun Kumar; V, Rajkumar; Vivekanand (Journal of Meat Science, 2025)
The present study was carried out to evaluate the effect of frying for different durations on quality attributes of shelf stable chicken pickle. Chicken pickle was prepared as per pre- established method. An attempt was made to improve the quality characteristics of chicken pickle by precooking of marinated meat by frying in mustard oil for 10, 15 and 20 minutes separately. The pH, fat and ash content as well as redness (a*) values increased significantly (P